The Kinetic Isotope Effect as a Probe of Spin Crossover in the CH Activation of Methane by the FeO+ Cation - Mai, Binh Khanh; Kim, Yongho (Angewandte Chemie International Edition, 2015)
Two‐state reactivity (TSR) is often used to explain the reaction of transition‐metal–oxo reagents in the bare form or in the complex form. The evidence of the TSR model typically comes from quantum‐mechanical calculations for energy profiles with a spin crossover in the rate‐limiting step. To prove the TSR concept, kinetic profiles for CH activation by the FeO+ cation were explored. A direct dynamics approach was used to generate potential energy surfaces of the sextet and quartet H‐transfers and rate constants and kinetic isotope effects (KIEs) were calculated using variational transition‐state theory including multidimensional tunneling. The minimum energy crossing point with very large spin–orbit coupling matrix element was very close to the intrinsic reaction paths of both sextet and quartet H‐transfers. Excellent agreement with experiments were obtained when the sextet reactant and quartet transition state were used with a spin crossover, which strongly support the TSR model. A direct dynamics approach was used to generate potential energy surfaces of the sextet and quartet H‐transfers for transition‐metal–oxo reagents. Variational transition‐state‐theory rate constants and kinetic isotope effects including multidimensional tunneling revealed that the reaction proceeds from the sextet reactant to quartet transition state with a spin crossover along the intrinsic reaction paths.